Implementation of Web Content Extraction of Structured Data Using DotNet Framework - Florence Dayana, M; Chidambaram, M (International Journal of Computer Sciences and Engineering, 2025)
This paper deals in Web Content Mining for extraction of structured data. While perusing the web, the client needs to experience numerous pages of the Internet, channel the information and download related records and documents. This errand of seeking and downloading is tedious. Now and again the look inquiries call for particular choice, say, restricting inquiry to few connections. To lessen the time spent by clients, a web extraction and capacity apparatus has been composed and executed in .Net framework, that robotizes the downloading task from a given client question. The Test Scenario has been given different catchphrases. The present work can be a valuable contribution to Web Manipulators, Staff, Students and Web Administrators in an Academic Environment.